Aging and Facial Changes-Documenting Clinical Signs, Part 2: Methods of Documentation of Facial Changes - Nkengne, Alex; Bertin, Christiane (Skinmed, 2016)
Skin metrology has emerged as a multidisciplinary approach for objectively documenting skin anatophysiologic aspects and transformations. Methods have been proposed to describe age-related changes of facial skin. Some of them capture information describing visible clinical signs of aging such as wrinkles, sagging, and pigmentation. These methods include but are not limited to digital imaging, 3-dimensional imaging, and colorimetry. Other methods focus more on structural or physiologic changes of underlying tissues, among these are reflectance confocal imaging, magnetic resonance imaging, and ultrasound imaging. Finally, a group of methods including corneometry and reviscometry are used to describe changes in skin properties. This contribution describes available methods for documenting age-related changes affecting the shape, texture, and color of the face.